Insufficient knowledge and inappropriate practices of emergency doctors towards tetanus prevention in trauma patients: a pilot survey - Yong Liu; Xichao Mo; Xiaxia Yu; Jinxin Wang; Jinfei Tian; Jun Kuang; Jie Peng (Taylor & Francis Group, 2020)
China has a shocking number of tetanus cases in the world, but little research has investigated doctors' knowledge of and practices in tetanus prophylaxis, especially tetanus vaccination. To this end, we conducted a pilot study on 197 emergency doctors using a mixed method of web-based (163; 82.8%) and paper-based (34; 17.2%) surveys. There was no difference between the two groups except for the percentage of doctors receiving a tetanus booster in the past 10 years and the responses to question 11. Surprisingly, only 28.9% of doctors had received formal training on tetanus immunization and only 21.3% had themselves received a tetanus vaccine booster in the past 10 years. Furthermore, only 14.2% of the respondents confirmed the availability of the tetanus vaccine in their respective institutions. Finally, the correct rates and Tetanus-immune-globulin (TIG)-only option rates for questions 11-15 were unsatisfactory. Our results showed that most emergency doctors' knowledge and practices strayed from the recommendations of Advisory Committee on Immunization Practices (ACIP): 1) TIG alone for most trauma patients instead of vaccine was an overused treatment approach. 2) Most of the emergency doctors lacked formal training on and knowledge of tetanus vaccination. 3) Even the emergency doctors themselves were not properly vaccinated. 4) The tetanus vaccine was only available in a small number of the respondents' institutions. The findings of this study suggest an urgent need to improve this dire situation.